Effects of Self-Leadership and Competence on Employee Performance Mediated by Extrinsic Motivation KPP Pratama Jember - Mohammad Hanafi Khoiron; Ika Barokah Suryaningsih; Etty Puji Lestasri (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study examines the effects of self-leadership and competence on employee performance, with extrinsic motivation as a mediating variable at KPP Pratama Jember. Using a quantitative explanatory design, data were collected from 93 employees (census sampling) through a structured questionnaire and analyzed using PLS-SEM. The results indicate that self-leadership and competence positively influence employee performance both directly and indirectly through extrinsic motivation. These findings support Self-Determination Theory and suggest that integrating self-leadership development, competency enhancement, and extrinsic motivational strategies is essential to improving performance in public-sector tax administration.